Improving risk identification process in project management - De Godoi Contessoto, Allan [UNESP]; Sant Ana, Laís Andreoli [UNESP]; De Souza, Rogéria Cristiane Gratão [UNESP]; Valêncio, Carlos Roberto [UNESP]; Donegá, Geraldo Francisco [UNESP]; Amorim, Anderson Rici [UNESP]; Esteca, Antonio Marcos Neves [UNESP] (KSI Research, 2016)
Nowadays there are many information systems which aim the decision-making, automating the processes of project management. However, many times these systems limit the specific functions related to risk management processes and do not allow the control and effective treatment of uncertain events that may affect the project goals. Thus, this paper proposes the integrated use of the Delphi Technique and Risk Breakdown Structure - RBS in order to contribute to the identification of risks, considering the opportunities and threats in a project, to enhance the beneficial effects of the opportunities and avoid the harmful effects of threats. For the evaluation of the results, it was performed the improvement of a system called System to Aid Project Managing - SAPM, in order to support the automated execution of risk management with an emphasis on risk identification process, since this is a crucial stage for risk management in projects. As a result of this work, it is observed that the combined use of the Delphi Technique and RBS allows the risk identification process can be performed fast and safely through the anonymity of those involved and global visualization of the project.
Keywords: Delphi technique; Risk breakdown structure; Risk management; System to aid project managing